Segmentasi Citra Spektrum Menggunakan Algoritma Region Growing - Marbun, Riccy Erwandy (TIN: Terapan Informatika Nusantara, 2021)
Image segmentation is a process shown to get the objects contained in the image or to divide the image into several areas with each object or area having similar attributes. The Region growing algorithm is a procedure that groups pixels or sub-regions into larger areas based on defined criteria. The basic approach starts from the set of starting points, then the area is enlarged by adding each neighboring pixel point that has similar properties to that point, for example the range specification intensity or color. The purpose of region-based segmentation (region) is to divide an image into several regions, this is done by grouping parts of the image that have the same characteristics in the form of color changes between adjacent points. The application of the Region Growing algorithm can be used in analyzing the segmentation of Infrared Spectrum Image in detecting image edges based on the growth area with the image segmentation process using the Region Growing algorithm